Discovery of tricyclic dipyrrolopyridine derivatives as novel JAK inhibitors. Issue 20 (15th October 2017) - Yamagishi, Hiroaki; Inoue, Takayuki; Nakajima, Yutaka; Maeda, Jun; Tominaga, Hiroaki; Usuda, Hiroyuki; Hondo, Takeshi; Moritomo, Ayako; Nakamori, Fumihiro; Ito, Misato; Nakamura, Koji; Morio, Hiroki; et al.
Graphical abstract: Abstract: Janus kinases (JAKs) play a crucial role in cytokine mediated signal transduction. JAK inhibitors have emerged as effective immunomodulative agents for the prevention of transplant rejection. We previously reported that the tricyclic imidazo-pyrrolopyridinone2 is a potent JAK inhibitor; however, it had poor oral absorption due to low membrane permeability. Here, we report the structural modification of compound2 into the tricyclic dipyrrolopyridine18a focusing on reduction of polar surface area (PSA), which exhibits potent in vitro activity, improved membrane permeability and good oral bioavailability. Compound18a showed efficacy in rat heterotopic cardiac transplants model.